TEACHER’S USE OF SCAFFOLDING IN ENGLISH SPEAKING LESSONS FOR MAINSTREAM FRESHMEN AT FELTE, ULIS = HOẠT ĐỘNG TẠO BƯỚC ĐỆM GỢI Ý (SCAFFOLDING) CỦA GIÁO VIÊN TRONG GIẢNG DẠY KỸ NĂNG NÓI CHO SINH VIÊN NĂM NHẤT CHUYÊN NGÀNH SƯ PHẠM TIẾNG ANH TẠI ĐẠI HỌC NGOẠI NGỮ - Vũ, Phương Hạnh (2020)
The current research aimed at identifying the scaffolding tools used by teachers in speaking lessons for FELTE freshmen and the reasons behind their choices of those tools as well as investigating the effectiveness of this practice from students' perspective. To attain those objectives, qualitative approach was adopted for data collection and analysis. Specifically, data was collected from five teachers and twenty-three students by means of two research instruments namely classroom observations and semi-structured interviews. Data analysis revealed that teachers utilized all six scaffolding tools in English speaking instruction for FELTE freshmen namely feeding back, hints, instructing, explaining, modelling and questioning. Of these, questioning was ranked as the most commonly used scaffolding tool whereas the other tools were observed with lower frequency. It is also noteworthy that more scaffolding was embedded in speaking instruction in English for Academic Purposes lessons than in English for Social Purposes lessons.